MicroRNA and mRNA expression profiling in metastatic melanoma reveal associations with BRAF mutation and patient prognosis. (5th January 2015) - Tembe, Varsha; Schramm, Sarah‐Jane; Stark, Mitchell S.; Patrick, Ellis; Jayaswal, Vivek; Tang, Yue Hang; Barbour, Andrew; Hayward, Nicholas K.; Thompson, John F.; Scolyer, Richard A.; Yang, Yee Hwa; Mann, Graham J.
Summary The role of microRNAs (miRNAs) in melanoma is unclear. We examined global miRNA expression profiles in fresh‐frozen metastatic melanomas in relation to clinical outcome and BRAF mutation, with validation in independent cohorts of tumours and sera. We integrated miRNA and mRNA information from the same samples and elucidated networks associated with outcome and mutation. Associations with prognosis were replicated for miR‐150‐5p, miR‐142‐3p and miR‐142‐5p. Co‐analysis of miRNA and mRNA uncovered a network associated with poor prognosis (PP) that paradoxically favoured expression of miRNAs opposing tumorigenesis. These miRNAs are likely part of an autoregulatory response to oncogenic drivers, rather than drivers themselves. Robust association of miR‐150‐5p and the miR‐142 duplex with good prognosis and earlier stage metastatic melanoma supports their potential as biomarkers. miRNAs overexpressed in association with PP in an autoregulatory fashion will not be suitable therapeutic targets.